Prevalensi tipe hubungan akar gigi posterior terhadap sinus maksilaris ditinjau dari radiografi panoramik - Ramadhanty, Adinda; Farizka, Intan (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Panoramic radiography is one of the supporting examinations commonly used in dentistry because it presents the maxilla and mandibula in one film, it can show all of the teeth and the surrounding anatomical structures, such as the maxillary sinus. The maxillary sinus is close to the maxillary posterior teeth roots. The close relation between both of them can lead to unwanted complications. There is a classification of the vertical relation type of the posterior teeth roots to the maxillary sinus, one of them is made by Sharan & Madjar which divides into 5 types. Objective: To determine the prevalence of the vertical relation type of the maxillary posterior teeth roots to the maxillary sinus on panoramic radiographs. Methods: Descriptive observational study with a cross-sectional approach with the purposive sampling method. The study samples are 204 of panoramic radiograph at RSGM-P FKG Usakti. The data are grouped into Sharan & Madjar then the prevalence of each tooth is calculated. Results: Overall results obtained that type 0 are 573 (35%), type 1 are 309 (19%), type 2 are 86 (5%), type 3 are 654 (40%) and type 4 are 10 (1%). Conclusion: The highest prevalence is in the type 3 and the lowest is in the type 4. In the first and second premolars, The highest prevalence is in the type 0 and the lowest is in the type 4. Meanwhile, in the first and second molars, the highest and lowest prevalence are found in the type 3 and type 4